Diagnostic Validity of Magnetic Resonance Imaging for the Detection of Ependymoma among Bangladeshi Children - Haque, Zerin; Alim, Md Abdul; Ahmed, Shaifur; Ahmed, Rokshana; Rahman, Meher Angez; Nahar, Nazmun (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Detection of ependymoma is very essential for the management of the patients. Objective: The purpose of the present study was to validate as well as to find out the Magnetic Resonance Imaging (MRI) findings of ependymoma among paediatric patients. Methodology: This cross-sectional study was carried out from January 2010 to June 2011 for a period of one year and six months in the Department of Radiology & Imaging at Dhaka Medical College, Dhaka, Bangladesh. Pediatric Patients having clinically suspected brain tumours of ependymoma variant who were undergone MRI of brain were included in this study. The pediatric patients clinically suspected for brain tumor in posterior cranial fossa region with the suspicion of ependymoma having no contraindication for MRI was underwent MRI examination. The postoperative resected tissues were examined histopathological in the respective department. All the clinical profiles and demographic data were collected. Result: This study included 33 patients with clinical features compatible with posterior fossa tumors. Out of all cases 4 cases were diagnosed as ependymoma in MRI and confirmed by histopathological evaluation. Out of 4 histologicaly proved cases, all cases were in ventricle. However, 2 cases were hypointense and 2 cases were isointense in TIWI and 3 cases were hyperintense in T2WI .3 cases are solid and 1 case was mixed. All cases had irregular margin and mass effect. All cases also had peri-lesional oedema. Marked enhancement was present in 3 cases. The sensitivity of MRI for the detection of ependymoma was 75.0% (95% CI 19.41% to 99.37%). However, the specificity of MRI was very high which was 96.5% (95% CI 82.24% to 99.91%). The positive predictive values and negative predictive value of MRI were 75.0% (95% CI 28.73% to 95.71%) and 96.5% (95% CI 83.66% to 99.35%) respectively. The accuracy was 93.9% (95% CI 79.77% to 99.26%). Conclusion: In conclusion accuracy of MRI for the detection of ependymoma is very high. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 147-151